2019
DOI: 10.32598/irj.17.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Transcranial Direct Current Stimulation (tDCS) on Methamphetamine Craving: A Randomized, Sham-controlled Study

Abstract: The modulation of the dorsolateral prefrontal cortex (DLPFC) activity enhanced the prospects of substance use disorders rehabilitation, using non-invasive brain stimulation, such as transcranial Direct Current Stimulation (tDCS). Methods: We carried out a randomized sham-controlled clinical trial to assess the effect of repeated tDCS at DLPFC on drug craving in 30 abstinent male methamphetamine users. The participants underwent 5 sessions of 20 minutes bilateral real or sham 2 mA tDCS (anode right/ cathode lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Six studies assessed either repetitive transcranial magnetic stimulation (rTMS) ( n = 4) or transcranial direct current stimulation (tDCS) ( n = 2) of the dorsolateral prefrontal cortex (DLPFC) to evaluate changes in cue-induced craving [ 40 , 48 , 49 , 50 , 51 , 52 ]. Li et al (2013) found low-frequency rTMS of 1 Hz to transiently increase cue-induced craving [ 48 ] while Su et al (2017) found high frequency rTMS of 10 Hz to reduce cue-induced craving in methamphetamine users [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies assessed either repetitive transcranial magnetic stimulation (rTMS) ( n = 4) or transcranial direct current stimulation (tDCS) ( n = 2) of the dorsolateral prefrontal cortex (DLPFC) to evaluate changes in cue-induced craving [ 40 , 48 , 49 , 50 , 51 , 52 ]. Li et al (2013) found low-frequency rTMS of 1 Hz to transiently increase cue-induced craving [ 48 ] while Su et al (2017) found high frequency rTMS of 10 Hz to reduce cue-induced craving in methamphetamine users [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…A single session of anodal tDCS on the right DLPFC decreased immediate subjective craving at rest after 10 min but increased craving rating upon exposure to methamphetamine cues compared to the sham condition, with the more provocative cues inducing significantly more cravings [ 50 ]. On the other hand, repeated sessions of bilateral tDCS (anodal stimulation of right hemisphere and cathodal stimulation of left hemisphere) reduced cue-induced craving but did not alter instant craving [ 51 ]. It was proposed that the different numbers of tDCS sessions or montages used by the two studies may have contributed to such discrepancy in findings [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methamphetamine craving was measured on a Visual Analog Scale (VAS). The study findings indicated that tDCS was effective in reducing self-reported craving in the treatment group while no significant changes were reported by the control group [14]. The study results are important; first because there are few similar research studies on tDCS in Iran [15][16][17][18].…”
Section: Studies In Iran Indicate That Methamphetamine Cravingmentioning
confidence: 87%
“…Recently, a study has been published by Rohani Anaraki and colleagues in Iranian Rehabilitation Journal [14]. Repeated transcranial Direct Current Stimulation (tDCS) was implemented on the brain cells of 30 men with methamphetamine dependence.…”
Section: Studies In Iran Indicate That Methamphetamine Cravingmentioning
confidence: 99%